Variação fonológica e lexical em Libras - Silva, Alan David Sousa (2020)
This research aims to describe and analyze linguistic variations in the Brazilian Sign Language (LIBRAS), used by deaf people from Maceió, guided by theoretical methodological assumptions from the perspective of Labovian Sociolinguistics. For this, it starts from a discussion about the lexicon in sign languages, considering the proposal of Fenlon et al (2017) and Brentari & Padden (2001), as well as the discussion about the parameters in sign languages, considering since the precursor study by Stokoe (1960) and a more recent study presented in Rosa et al. (2016). Methodologically, we followed the Theory of Linguistic Variation (LABOV, 1972), considering extralinguistic variables, education, sex and age group, to control the observed variations, in order to verify whether these variables would be correlated to different linguistic uses. The corpus of analysis was constituted considering three age groups: up to 29 years of age; between 30 to 49 years; over 50 years old, with 2 men and 2 women in each range. The study focuses on variations in eight signs in Libras referring to the lexical fields color and food. All participants are deaf from Maceió, capital of Alagoas, and the data that constituted the research corpus were made available and selected from the National Inventory of Brazilian Sign Language Project of the Institute for Research and Development of Linguistic Policy, therefore the methodology of data collection is that adopted by the referred project. The analysis points out that there are no significant differences in variation that may be correlated to the gender variable, however, there is a signaling of the education variable related to the use of certain forms. In this sense, the results showed that deaf people with higher education tend to produce variants with loan of hand configuration representing letters of the alphabet of the Portuguese language. Regarding the age group variable, it was also possible to verify a correlation between this variable and the use of signs. In this sense, for example, the variant for WHITE performed with the closed non-dominant hand was more used by younger people, while elderly people used the open non-dominant hand for this sign, a case classified as a variation in the phonological level, as it is just change in a single parameter. Also in relation to lexical variation, different uses were observed in relation to the age group, as was observed, for example, in the use of the sign referring to PASSION FRUIT.